Genologia lingwistyczna a badania nad komentarzem e-sportowym (problemy metodologiczne) - Rzeźnik, Martyna (Replay. The Polish Journal of Game Studies, 2018)
Video games are a crucial part of contemporary reality. Their popularity has contributed to the appearance of the esports scene, and thus to the emergence of a new media genre: the esports commentary. In this paper I apply Maria Wojtak’s method of genological research to analyze the esports commentary to the game sessions of Counter Strike: Global Offensive. In accordance with the author’s premises I examine four genre aspects. The first is structure, i.e., the delimitative framework as well as particular segments which make up the entire commentary. The next aspect, the pragmatic one, concerns the relationship between the addresser (commentator) and the addressee (Internet user). What is also needed is a description of the cognitive aspect, i.e., subject matter, valuation, and other elements of the genre’s lingual image of the world. The final aspect is the characteristic stylistic traits of the esports commentary, such as its colloquial nature, its emotionality, or its jargon vocabulary. The main conclusion of the paper is that it is suitable to adapt Maria Wojtak’s method to the research into esports commentary as a new media genre.